New Belgium Brewing: What Is Its Future After the Acquisition? - Hoffman, David Lynn; Gilliard, Debora J.; Baalbaki, Sally (Journal of Marketing Development and Competitiveness, 2022)
This case explores the rise of New Belgium Brewing from inception to a well-known brewery, the founders’ passion, its concern for environmental issues, and its employee involvement in management which led to an employee purchase via an ESOP. In 2019 the employees voted to sell to Lion Little World Beverages of Australia, a subsidiary of Kirin. The questions going forward are will the company maintain its passion for environmental issues, social challenges, and employee involvement? Can or will the new owner maintain the previous culture?